Choroidal Confusions: A look into Pachychoroid Spectrum of Diseases - Panchal, Sonia; Acharya, Rajni; Saucedo, Erika (Canadian Journal of Optometry, 2023)
ABSTRACT A 59-year-old African American male presented for a comprehensive eye examination. His pertinent ocular history was extensive and included a past occurrence of Central Serous Chorioretinopathy (CSCR) in the left eye (OS), presumed macular toxicity of the right eye (OD) due to Plaquenil therapy for Rheumatoid Arthritis, and presumed Advanced-stage Dry Age-related Macular Degeneration (ARMD) of both eyes. Stargardt’s Disease was also listed as a differential diagnosis for the patient under his ocular history. Upon clinical review and additional ancillary testing, we determined the patient did not have Macular Degeneration, Stargardt’s, or Plaquenil toxicity, and rather, fell into the category of a pachychoroid disease. Pachychoroid spectrum is often overlooked by clinicians as it is a group of conditions and therefore can masquerade several commonly thought of diseases, such as ARMD, Bull’s eye maculopathy, and Stargardt’s Disease. The use of Optical Coherence Tomography (OCT) and Fundus Autoflourescent (FAF) photography helps in distinguishing between these differentials to rule-in a pachychoroid disease. Understanding these conditions can help avoid misdiagnoses and allow for more appropriate management of our patients.